Comparison of Long-term Outcomes Associated With Endovascular Treatment vs Surgical Treatment Among Medicare Beneficiaries With Unruptured Intracranial Aneurysms. Issue 4 (30th May 2014) - Qureshi, Adnan I.; Chaudhry, Saqib A.; Tekle, Wondwossen G.; Suri, M. Fareed K.
Abstract: BACKGROUND: Long-term outcomes associated with endovascular and surgical treatments for unruptured intracranial aneurysms are not well studied to date. OBJECTIVE: To determine the 5-year risk of new intracranial hemorrhage, second procedure, and all-cause mortality in elderly patients with unruptured intracranial aneurysms who underwent either surgical or endovascular treatment. METHODS: The study cohort included a representative sample of fee-for-service Medicare beneficiaries aged ≥65 years who underwent endovascular or surgical treatment for unruptured intracranial aneurysms with postprocedure follow-up of 4.7 (±3.0) years. Cox proportional hazards analysis was used to assess the relative risk (RR) of all-cause mortality, new intracranial hemorrhage, or second procedure for patients who underwent endovascular treatment compared with those who underwent surgical treatment after adjusting for potential confounders. The 5-year survival was estimated for both treatment groups by using Kaplan-Meier survival methods. RESULTS: A total of 688 patients with unruptured intracranial aneurysms were treated with either endovascular (n = 398) or surgical treatment (n = 290). The rate of immediate postprocedural neurological complications (10.3% vs 3.5%, P = .001) was higher among patients treated with surgery than among those who underwent endovascular treatment. The estimated 5-year survival was 92.8% and 94.8% in patients who underwent surgical and endovascular treatments, respectively. After adjusting for age, sex, and race/ethnicity, the RRs of all-cause mortality (RR, 0.6; 95% confidence interval, 0.3-1.1) and new intracranial hemorrhage (RR, 0.4; 95% confidence interval, 0.2-0.8) were lower with endovascular treatment. CONCLUSION: In elderly patients with unruptured intracranial aneurysms, endovascular treatment was associated with lower rates of acute adverse events and long-term all-cause mortality and new intracranial hemorrhages.